Pengaruh Kualitas Pelayanan, Harga, Lifestyle Dan Brand Image Terhadap Kepuasan Konsumen Pada Toko Eiger Rantauprapat - Zahara, Inti; Hendry, Raja Saul Marto; Asnora, Fadzil Hanafi (Jurnal Manajemen Akuntansi (JUMSI), 2024)
The purpose of this study evaluates how service quality, price, lifestyle, and brand image affect how small and medium enterprises in Labuhanbatu use accounting data. With a sample size of 100 people, the Slovin equation was used as the sampling method. To collect data, 100 questionnaires were sent to consumers in the form of Google Forms. Multiple regression with SPSS 23 was used in data analysis. The results showed that service quality and price have a positive and significant effect on consumer satisfaction and for lifesytle and brand image there is also a negative effect on consumer satisfaction. However, consumer satisfaction does not depend on lifestyle and brand image.